MODERN METHODS OF PREVENTING TRAFFIC ON CENTRAL CITY STREETS - Nazarov Anvar Aripovich; Suyarov Nurali Zhovli ugli (Web of Journals Publishing, 2026)
This article analyzes the negative impact of several factors on road capacity. The factors causing traffic jams were studied and analyzed based on the results of research and inspections.
Keywords: Traffic jams, road traffic accidents, research on the impact on capacity, hazards, trees, buildings, winter and summer, driver, sharply limiting capacity, Road surveillance.